Co-transport of Pb (II) and Cd (II) in saturated porous media: effects of colloids, flow rate and grain size. Issue 1 (1st January 2018) - Xie, Bingyi; Jiang, Yanji; Zhang, Zhe; Cao, Gang; Sun, Huimin; Wang, Nong; Wang, Shengsen
ABSTRACT: The transport of Pb(II) or Cd(II) in subsurface has been studied in the literature; however; their co-transport in porous media in presence of colloids has not been clearly understood. In this work, a series of column experiments were conducted to study Pb(II) and Cd(II) co-transport in saturated porous media under various experimental conditions with different combination of colloidal solution (montmorillonite colloid, manual loessial soil colloid and humic acid), flow rate (0.1, 0.5 and 1.0 ml min −1 ) and sand grain size (0.4–0.8mm and 0.8–2.0mm). The results showed that increase of flow rate and grain size promoted the mobility of Pb(II) and Cd(II), furthermore, the presences of mobile colloids also enhanced the mobility of the two heavy metals, meanwhile, Cd(II) showed higher mobility than Pb(II) in the columns. Findings from this work enhanced current understanding of the competitive transport and colloid-facilitated transport of heavy metals in saturated porous media.